The effect of the (s.a.m.r) model using special exercises in learning the two skills of scoring from the free and peaceful throw line in basketball. (Journal of the College of Basic Education, 2022)
The effect of the (s.a.m.r) model using special exercises to learn the two scoring skills from the free throw line and the paddle line with basketball.The first chapter included the definition of the research, the introduction, the importance of the research, the research problem, and the objectives of the research, which are:- Preparing special educational units using the (samr) model, using special exercises to learn offensive skills in basketball, and identifying the effect of the samr model, accompanied by special exercises in learning some offensive skills in basketball, and identifying the preference of which two groups are better in learning some offensive skills The second chapter includes the curriculum used, which is the experimental curriculum, the community and the research sample. The research sample was chosen from the original community by the deliberate method represented by second-grade students in the Department of Physical Education and Sports Sciences - College of Basic Education - Al-Mustansiriya University for the academic year 2020-2021 of which the total number is ( 145) and by (4) divisions represented the research sample, which was chosen in a systematic random way. It was selected from the original community of (80) students, and they are class (A) (B) and by lottery, Division (B) became (45) students of the experimental group. And Division (A), totaling (35) students, a control group. (4) female students were excluded from the two divisions, and (11) students were excluded from Division (B) and (5) students from (A) class, and that did not comply with attendance and lack of commitment. Their mother was constantly and then postponed for the academic year, and thus the research sample became (60) students distributed evenly between the two groups. The homogeneity was conducted and the exploratory experiment was conducted on a sample while they were outside the research sample. The scientific basis for the tests was extracted and found that it has a high degree of honesty, consistency and objectivity, after which the tests were conducted. The tribal experiment was applied using the model according to special skill exercises, after which the dimensional tests were carried out, and the fourth chapter included the conclusions reached by the research, which are:- The results showed the superiority of the experimental group that used the (s.a.m.r) model in combination with his skill exercises in learning some skills in basketball.- The proposed educational units that were used by the experimental group, which included the use of the educational technology integration model (s.a.m.r) in combination with skill exercises that had a positive effect on learning offensive skills in basketball (chest handling, high puckering, scoring from the free throw line, peaceful scoring